FORMALISASI SYARIAT ISLAM DAN HAK ASASI MANUSIA DI INDONESIA - AR, Yusdani (Islamic University of Indonesia, 2006)
The article below tries to trace the problem of syariah formalization and human rights in Indonesia. Several issues will emerge in the context of syariah formalization, for instance, the interpretation of syariah, the freedom of religion, the position of non-Moslem, the role of woman, the religious community conflict, and the crisis of the constitution. Based on the issues mentioned above, the the writer of the following article revealed that the formalization of syariah should need new humanistic interpretation and iit also consider and accomadate human rights issues recently. Kata kunci: syariat Islam, formalisasi, HAM, dan interpretasi.